2022
DOI: 10.1002/job.2629
|View full text |Cite
|
Sign up to set email alerts
|

Laughing with me or laughing at me? The differential effects of leader humor expressions on follower status and influence at work

Abstract: Although research suggests that leader humor shapes followers' perceptions of their leaders' status, questions remain as to whether and how leader humor can shape followers' own acquisition of status at work. Drawing from the approach-avoidance framework, we provide an important extension to the leader humor literature by developing a serial mediation model that explains how and why two styles of leader humor-aggressive humor and affiliative humor-differentially impact followers' ability to garner and wield so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 84 publications
0
32
0
Order By: Relevance
“…In this research, we are interested in humor as a behavior rather than sense of humor as a trait ( Martin and Lefcourt, 1984 ), as this definition is broad enough to include all types and forms of humor (e.g., affiliative humor, visual images) ( Cooper, 2008 ) and also captures interpersonal phenomenon through actor sharing and target perceiving ( Cooper, 2005 ), which is appropriate in our research. In line with prior work ( Pundt and Herrmann, 2015 ; Kim et al, 2016 ; Cooper et al, 2018 ; Carnevale et al, 2022 ), we consider leader humor at the individual level because members of the same work group may have different perceptions of their leader’s humor. Past research has illustrated the positive effects of leader humor on job satisfaction, organizational citizenship behavior, and team performance ( Hughes and Avey, 2009 ; Mao et al, 2017 ; Cooper et al, 2018 ).…”
Section: Theory and Hypotheses Developmentmentioning
confidence: 99%
“…In this research, we are interested in humor as a behavior rather than sense of humor as a trait ( Martin and Lefcourt, 1984 ), as this definition is broad enough to include all types and forms of humor (e.g., affiliative humor, visual images) ( Cooper, 2008 ) and also captures interpersonal phenomenon through actor sharing and target perceiving ( Cooper, 2005 ), which is appropriate in our research. In line with prior work ( Pundt and Herrmann, 2015 ; Kim et al, 2016 ; Cooper et al, 2018 ; Carnevale et al, 2022 ), we consider leader humor at the individual level because members of the same work group may have different perceptions of their leader’s humor. Past research has illustrated the positive effects of leader humor on job satisfaction, organizational citizenship behavior, and team performance ( Hughes and Avey, 2009 ; Mao et al, 2017 ; Cooper et al, 2018 ).…”
Section: Theory and Hypotheses Developmentmentioning
confidence: 99%
“…When leaders remove barriers to hierarchical communication (Lapointe and Vandenberghe, 2018), they create an organizational climate of trust and psychological safety where employees feel safe not only to share advice with colleagues, but more importantly to ask work-related questions (Weiss et al, 2018). Leader personality traits may have indirect effects, positive or negative, on members' voice and work engagement with workplace status (Carnevale et al, 2022;Park et al, 2022;Wang et al, 2022). Research has found that leaders' threats to judge employees' voices can lead to lower performance appraisals of employees (Weiss & Morrison, 2019;Xu et al, 2019), so employees may change their voiceover styles in line with their supervisors' perceptions of workplace behavior (Ng et al, 2022; Park et al, 2022.…”
Section: Leadership Stylesmentioning
confidence: 99%
“…Second, drawing from the sociometer theory, we propose feeling ostracized as the specific intermediary mechanism that links leader aggressive humor to employee extra-role behaviors. In so doing, we enrich the fruitful effort of recent theoretical attempts to comprehend leader aggressive humor from the approach-avoidance perspective (Carnevale et al. , 2022), social exchange perspective (Liu et al.…”
Section: Introductionmentioning
confidence: 96%
“…(2003) argue that leader aggressive humor is always intended to tease and “put down” subordinates to display a leader's superiority without regard for the painful impact on followers. Although scholars have posited that leader aggressive humor is a maladaptive behavior that leads to adverse impacts on employees, such as suppressing employee voice (Carnevale et al. , 2022; Liu et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation